Cloud Radio Random-Access Networks With Multi-Packet Reception Capability - Cheolkyu Shin; Seok-Hwan Park; Junghyun Kim; Hyuncheol Park (IEEE Access, 2024)
Cloud Radio Access Network (C-RAN) refers to the virtualization of base station functionalities by means of cloud computing. With centralized processing at the cloud, the amount of hardware and infrastructure in a network can be reduced and it allows for operators to save expenses needed to deploy and maintain the network. Along with high spectral and energy efficiency, C-RAN becomes a key technology evolving to 5G network and it is also expected to play a critical role in the next generation of wireless network. In this paper, theoretical expressions are derived for throughput performance at Medium Access Control (MAC) layer with and without Cloud Radio Random-Access (CRRA). We first develop a CRRA protocol by accounting for the Multi-Packet Reception (MPR) capabilities afforded thanks to the deployment of C-RAN. We then analyze the throughput performance based on error exponent analysis. Numerical results show the performance advantages of C-RAN and verify theoretical expressions.